Gulburra (to understand): Aboriginal Ability Linker's person-centred care approach. Issue 19 (11th September 2021) - Gibson, Chontel; Chatfeild, Katy; O'Neill-Baker, Bryce; Newman, Tracey; Steele, Annette
Abstract: Introduction: Aboriginal and Torres Strait Islander people are experts and advocates in disability services. The Aboriginal Ability Links Program is one example where this expertise and advocacy occurs. The primary aim of the Aboriginal Ability Links Program is to support Aboriginal people, who live with a disability, to connect with family, communities and services, build confidence, work towards goals, and plan for the future. This program is guided by a set of principles, one of which includes the application of person-centred care approaches. This project explores person-centred care approaches used in one service, which is delivering the Aboriginal Ability Links Program. Methods: Key in this Community Based Participatory Research was Aboriginal leadership, guidance, and participation. This project used yarning for data collection and thematic analysis for data analysis. Multiple yarning sessions took place, and five case scenarios were developed. Three Aboriginal Ability Linkers were involved in the research yarning sessions, as was the manager of the service. Consultation yarning sessions with additional Aboriginal Ability Linkers, as well as other managers and an Elders group confirmed the results of this project. Results: The results revealed the person-centred care approach used by Aboriginal Ability Linkers. This person-centred care approach included: have a yarn and connect with culture; connect with community, including elders; critically reflect on yourself and your practice; be trauma informed and aware of contexts; encourage voices and choices, and finally, strengthen relationships with and between key stakeholders. Conclusion: Aboriginal Ability Linkers provide essential services, which promote a strength-based approach and culturally responsive services with Aboriginal communities. This person-centred approach can be applied in other disability and disability-related settings. IMPLICATIONS FOR REHABILITATION: This person-centred care approach offers disability services providers a framework for working with Aboriginal people. The person-centred care approach incorporates Aboriginal philosophical approaches and builds on the previous work of Aboriginal disability scholars. This person-centred care approach is embedded in a decolonising framework and as such, guides disability workers to reflect on themselves, the Australian context and the impact of trauma in Aboriginal communities.